Failure to achieve asepsis following surgical skin preparation is influenced by bacterial resistance to chlorhexidine, but not skin preparation technique. Issue 8 (3rd August 2017) - Swales, Nicola; Cogan, Tristan
Abstract: Samples were taken before and after skin preparation in 25 dogs undergoing abdominal surgery. Bacterial culture and sensitivity testing was undertaken. Eight of 25 dogs had bacteria present after preparation, of which three were prepared using the concentric circle and five using the linear method. There was no significant difference in the efficacy in achieving asepsis of either method. Four of 10 bacterial isolates remaining after surgery were resistant to chlorhexidine; two were resistant to chlorhexidine at the concentration at which it was used for skin preparation. Chlorhexidine resistance is a risk factor for the presence of bacteria post-preparation.